THU0383 Incidence of uveitis in non-steroidal anti-inflammatory drugs versus tumor necrosis factor inhibitors users among patients with ankylosing spondylitis: a retrospective cohort study. (15th June 2017) - Kim, MJ; Lee, EE; Lee, EY; Song, YW; Lee, EB
Abstract : Background: Uveitis associated with ankylosing spondylitis (AS) often recurs and may lead to ocular complications. It remains to be known whether non-steroidal anti-inflammatory drugs (NSAIDs) or TNF inhibitors (TNFi) is more effective in reducing the recurrence of uveitis in patients with AS. Objectives: To evaluate the effect of NSAIDs and TNFi on preventing recurrence of uveitis in patients with AS. Methods: This retrospective cohort study included 1061 patients diagnosed with AS at Seoul National University Hospital between January 2004 and December 2015. Patients' clinical factors and laboratory findings were collected from the patients' electric medical records. Patients were divided into those who were treated with NSAIDs (n=623) or TNFi (n=438) which included etanercept, adalimumab, infliximab and golimumab. The incidence rates of new-onset uveitis during each treatment was compared using Cox proportional hazard model after adjusting age, sex, disease duration, history of uveitis, smoking status, ESR, CRP, and HLA-B27. Propensity-score matched comparison was also performed as sensitivity analysis (n=168 in the TNFi group and n=168 in the NSAID group). Results: Among the 1061 patients, those in the TNFi group had longer disease duration (11.75±7.14 vs 6.22±4.42 years), higher ESR, CRP level (40.97±33.87 vs 23.32±22.09 mm/h, 2.69±3.41 vs 1.12±1.93 mg/L, respectively) and higher proportion of patients who had previous history of uveitis before the treatment (22.4 vs 15.4%). The incidence rates of uveitis were 3.60 (95% CI 2.97 to 4.42) per 100 person-year in the NSAID group and 6.03 (95% CI 5.15 to 7.04) per 100 person-year in the TNFi group. The adjusted hazard ratio for the new-onset uveitis during the treatment in the TNFi group versus the NSAID group was 1.28 (95% CI 0.80 to 2.06) (p=0.304). When compared with NSAID group, etanercept group showed higher incidence of uveitis than the other TNFi: etanercept (HR 1.96 [1.41 to 2.74]), adalimumab (HR 0.65 [0.40 to 1.05]), infliximab (HR 0.50 [0.22 to 1.14]) and golimumab (HR 0.79 [0.25 to 2.50]). The propensity score-matched population was also consistent with the crude comparison between NSAID group and TNFi group (HR 1.29 [0.73 to 2.28]) (p=0.388). Conclusions: The effect of TNFi on reducing the incidence of uveitis is comparable to NSAIDs in patients with AS. Uveitis occurred more commonly with treatment with etanercept compared with the other treatments. Disclosure of Interest: None declared